2003
DOI: 10.1021/nl034317j
|View full text |Cite
|
Sign up to set email alerts
|

Relating Substitution to Single-Chain Conformation and Aggregation in Poly(p-phenylene Vinylene) Films

Abstract: The morphology of films of PPV derivatives is studied with molecular (single chain) resolution by phase-imaging scanning force microscopy. It is found that the symmetry of substitution is directly related to surface morphology and aggregation behavior. The molecular resolution in the phase contrast is shown to result from van der Waals interaction between the conjugated backbone of the polymer chains and the metallic tip, and can quantitatively be described by a simple harmonic oscillator model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 15 publications
6
53
1
1
Order By: Relevance
“…Both atomistic scale MD and Monte-Carlo calculations consistently portray this connected ring-forming structure formation of MDMO-PPV (Figure 9) (Kemerink et al, 2003). The bending force present in MDMO-PPV can be explained by an interaction, either attractive or repulsive, between the aliphatic side chains of successive monomer units.…”
Section: Some Other Materials Used In Opvsmentioning
confidence: 67%
See 1 more Smart Citation
“…Both atomistic scale MD and Monte-Carlo calculations consistently portray this connected ring-forming structure formation of MDMO-PPV (Figure 9) (Kemerink et al, 2003). The bending force present in MDMO-PPV can be explained by an interaction, either attractive or repulsive, between the aliphatic side chains of successive monomer units.…”
Section: Some Other Materials Used In Opvsmentioning
confidence: 67%
“…These seemingly connected rings could be due to the presence of a conformational or configurational defect. At such a defect, the orientation of the side chain is flipped from one side of the polymer chain to the other, and the bending direction is reversed (Kemerink et al, 2003). This molecular conformation and the weakly ordered stacking of the molecules, which result in a high disorder energy and poor π − π interaction, might be the origin of the poor transport properties in MDMO-PPV.…”
Section: Some Other Materials Used In Opvsmentioning
confidence: 99%
“…To gain more insight in the nature of the coiled-up conformations that are observed for OC 1 C 10 -and MEH-PPV, molecular dynamics calculations were performed on the former polymer. 23 In our previous work 14 we have shown that OC 1 C 10 macromolecules have a clear tendency to bend, a tendency that is absent in BisOC 10 macromolecules. Moreover, we have found that, in the absence of conformational defects, the coil is indeed the conformation with the lowest energy in these calculations.…”
Section: Resultsmentioning
confidence: 93%
“…In the case of OC 1 C 10 -PPV these chains have a coiled-up, spiraling conformation or, in the case of BisOC 10 -PPV, have a straight conformation. 14 The coiled-up conformation is illustrated in the insets of Figure 4c. The difference was tentatively attributed to the different symmetry of the substitution pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation